Analisis variabel yang mempengaruhi kinerja neraca transaksi berjalan Indonesia periode 2006-2020 - Noraditha, Yelinda; Heriberta, Heriberta; Emilia, Emilia (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This study aims to analyze whether the exchange rate, export, and import value affect Indonesia's current account balance. Using the Error Correction Model (ECM) analysis method. The results of this study partially show that the variable exchange rate and import value have a negative and significant on the current account balance variable in the long term; partially, the exchange rate variable has a negative and insignificant on the current account balance in the short time, partially the import value variable has a negative and significant on the current account balance in the short time, partially the export value variable has a positive and significant impact on the current account balance in the long term, and the short term and simultaneously the three independent variables have a positive and effective on the dependent variable in a long time and the short term.